Polypharmacy, Drug-drug Interaction and Potentially Inappropriate Medication in Hospitalized Elderly Patients with Cardiovascular Diseases in Wangaya Hospital - Septiani, Ana Maulida; Rahmawati, Fita (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Cardiovascular diseases (CVDs) are common diseases in the elderly as aging can cause changes in the heart and blood vessels. Patients with CVD are prone to multimorbid conditions which lead to the use of multiple medications (polypharmacy). Polypharmacy is susceptible to drug-drug interaction (DDI) and potentially inappropriate medication (PIM). This study aimed to identify polypharmacy, DDI, and PIM in hospitalized elderly patients with CVD. The design of this study is retrospective cross-sectional. A number of 100 medical records were employed and analyzed descriptively. Polypharmacy is defined as administering multiple medications at the same time or excessive medication administration of ≥4 drugs or ≥5 drugs. Potential DDI was detected by Lexicomp Application. PIM was identified based on Beers criteria 2019. The findings showed that most patients were male (55%) and aged 60-70 (72%). Most of the patients (48%) were categorized as moderate polypharmacy (8-10 medications/day). Potential DDI was revealed in 97% of patients, and Beers Criteria 2019 identified 280 cases of PIM. The study showed that polypharmacy, DDI, and PIM frequently occurred in hospitalized elderly patients with CVD. Pharmacists should pay more attention to reviewing the prescription. Therefore, the process of pharmacotherapy can be optimized and increase safety for elderly patients with CVDs.